Improved localized surface plasmon resonance responses of multi-metallic Ag/Pt/Au/Pd nanostructures: systematic study on the fabrication mechanism and localized surface plasmon resonance properties by solid-state dewetting - M Sui; S Kunwar; P Pandey; S Pandit; J Lee (New Journal of Physics, 2019)
Multi-metallic nanoparticles (NPs) can offer dynamic and tunable localized surface plasmon resonance (LSPR) properties that are suitable for various catalysis, sensing and energy harvesting applications due to the wide range of tunability and applicability. In this work, the systematic fabrication and improved LSPR characteristics of multi-metallic alloy NP arrays are demonstrated based on the solid-state dewetting (SSD) of multi-layers of Ag/Pt/Au/Pd on sapphire (0001). The evolution of surface NPs in terms of configurational and elemental specifications yields vary strong and dynamic LSPR bands in the UV and VIS wavelengths based on the excitation of various plasmonic modes, i.e. dipolar (DR), quadrupolar (QR), multipolar (MR) and higher order (HO) bands, which is further exploited by the finite difference time domain simulations. Through the systematic control of multi-layer thickness, layer ratio and growth conditions, various nanostructures such as voided nanoclusters, network-like NPs and isolated semispherical NPs are obtained, which are unique in terms of morphology and elemental composition at each stage of dewetting process. The growth mechanism of multi-metallic alloy NP arrays is proposed based on the temperature driven thermal diffusion, alloying, Rayleigh-like instability and energy minimization mechanisms. Due to the subsequent sublimation of Ag atoms at above 650 °C, a sharp alteration in the elemental and morphological characteristics is demonstrated. In specific, the high percentage of Ag alloy NPs exhibits strong LSPR bands and gradually weakened along with the Ag sublimation. At the same time, however, the alloy or mono-metallic NPs without Ag still demonstrate much stronger LSPR bands as compared to the monometallic NPs by the SSD of pure films.